Health and Wealth - Simon Anastasiadis (New Zealand Government, The Treasury, 2010)
This paper analyses the relationship between net wealth and health using Waves 1 to 3 of the Survey of Family, Income and Employment (SoFIE). The results show that lower net wealth is associated with worse health over a range of differing measures of health. The paper acknowledges but does not attempt to resolve the complex issue of causality; does health cause wealth or vice versa? Physical and mental wellbeing were both found to be positively associated with net wealth. These measures of wellbeing were decomposed by the occurrence of a health failure, defined as an injury or illness lasting more than one week. The results led to further inspection of the characteristics associated with health failures. This revealed that those who experienced a health failure had, on average, less wealth and worse self-rated health than those who did not. The progressive nature of poor health and lower net wealth was reinforced by considering self-rated health. There was a clear negative relationship between poor self-rated health and lower net wealth over the five categories of self-rated health. A series of chronic health conditions were also examined. The presence of these conditions was associated with lower net wealth though certain conditions were not always significant. Other than the presence of depression or schizophrenia, each chronic condition was decomposed by age of diagnosis revealing that asthma is more significant in the short term. For conditions other than asthma the coefficients were not significantly different. The analysis of wealth excluded those with zero or negative values for their wealth. To provide a more complete picture, the probability of having zero or negative net wealth was modelled. This revealed that individuals reporting poorer health were more likely to have non-positive net wealth. This study has relied on cross-sectional data from SoFIE. Once the full eight years of longitudinal data become available, a richer analysis of the impact of changes in health status over time on assets, liabilities and net wealth will be possible.
Keywords: D31; I10; 330; Health; Wealth; New Zealand; Self-reported health measures; Chronic illness; Gesundheit; Chronische Krankheit; Soziale Lage; Neuseeland